Theoretical and methodological foundations of the political element study as the phenomenon of social being: the theories of unity and conflict - VOLCHKOVA, OLGA OLEGOVNA; KRASNOV, ANTON SERGEEVICH (The journal of contemporary issues in business and government, 2020)
The study of the political element as the phenomenon of social life is possible only in the form of an appeal to ontological principles. Speaking about "political" in our study, we turn to a scientific discipline - political ontology. Political ontology in the most general view studies the problems of the political world being, its various forms of expression and essential characteristics. Besides, the purpose of the study in the mainstream of political ontology is to identify the patterns in power relation development, the interaction of various political actors in society within a multifaceted political reality. The status of political ontology as an independent study area is often questioned, and despite the fact that nowadays the academic community for the most part recognizes political ontology as an autonomous sphere, endowing it with the status of one of the basic disciplines for socio-political space study in on the whole, the discussions on the speculative nature of political-ontological research are still ongoing (Blaser, 2014). Political ontology is recognized as a system-forming role in the study of political space, and its formation as a paradigmatic basis for the study of any political and social phenomena and processes is considered as a subject area (Hay, 2006). Thus, the study of the political element as the phenomenon of social life is possible only in the form of an appeal to dogmatic principles and attitudes formed by political ontology..